English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

guys, i really hate math but i guess i need to deal with it right?!?! please help me im confused..>> answer this please>
5x+10-6x+3=6-2x-2 answer please and explaine

2006-11-04 11:01:42 · 11 answers · asked by chinita 2 in Science & Mathematics Mathematics

11 answers

Problem: find x in
5x+10-6x+3=6-2x-2

When we have with equation to do it important to know that we are allowed to subtract , add and multiply on both side of the equation as long as we do it simultaneously

first we try to reduce the expression as much as possible and on left side it's obvious that
5x-6x=-x and 10+3 =13
on right side it's obvious that
6-2=4
using these result by putting it in to the equation we become
13-x=4-2x

now we can add 2x to both side of the equation and we will get
13+x=4
now we add -13 to both side of the equation and become
x=4-13=-9
result
x= -9
===

2006-11-04 11:24:25 · answer #1 · answered by Broden 4 · 0 0

Simplify first, by adding up all the terms in x and by adding the numbers. The terms in x, such as 5x, can be added to the -6x because they are similar to one another. You cannot add 5x to 10 to get anything other than 5x + 10, because they are completely different things.

5x + 10 - 6x + 3 = 6 - 2x - 2

On the left-hand side, 5x - 6x = -x
and 10 + 3 = 13
So the left-hand side becomes
-x + 13

On the right-hand side, 6 - 2 = 4
so the right-hand side becomes
4 - 2x

Now the equation becomes :
-x + 13 = 4 - 2x

Now you need to get the x-terms on one side and the numbers on the other side. It's conventional to put the x-terms on the left.

If you add 2x to both sides, that will make the -2x on the right disappear, because 2x - 2x = 0. Remember that you have to add the same thing to both sides, otherwise the equation will become untrue. For example, in the true equation, 6 = 6, if you add 1 to the left side, you'll get 7 = 6, which is untrue, so you have to add 1 to both sides to make 7 = 7, which is still true.

So now, adding 2x to both sides gives :
2x - x + 13 = 4 - 2x + 2x

Simplifying again gives :
x + 13 = 4

To leave just x on the left, you have to get rid of the 13. It can be subtracted, but don't forget to subtract 13 from the right side also.

This gives :
x + 13 - 13 = 4 - 13
which leaves
x = -9, as the final answer.

2006-11-04 11:43:21 · answer #2 · answered by falzoon 7 · 0 0

OK, I think that looks more complicated than it is. I'm going to simplify it. As you read this, remember that what I'm trying to do is get every term containing x on the left, and all the terms that are just numbers on the right.

I see that there's a term with x--2x--on the right. I need to get rid of it. If I added 2x from that side, it would cancel out the addition of 2x. I have to add 2x from the left side too, to keep them equal. Anything I do to one side I have to do to the other. So the equation now is 5x + 10 - 6x + 3 + 2x = 6 - 2.

The right side is all numbers now, so let's look at the left. There are two numbers there that aren't multiplied by x: 10 and 3. They're being added, so we can cancel them by subtracting them from both sides. That gives the equation 5x -6x -2x = 6 -2 -10 -3.

Now we've got all the x's on the left and all the numbers on the right. The next thing to do is to get each side down to one term. Remember, you can add variables just like numbers, so 5x - 6x + 2x is the same as (5 - 6 + 2)x. So the left side becomes x. The right side is 6 -2 -10 -3, which is -9. So x = -9.

2006-11-04 11:13:23 · answer #3 · answered by Amy F 5 · 0 0

In fact there is no problem in this problem. It seems you are confused with the numerous solutions. Simply you move all the factors with 'x' to one side and the numerals to the other - you got the answer -
5x - 6x +2x = 6 - 2 -10 -3
x = -9

2006-11-05 00:11:41 · answer #4 · answered by Alrahcam 4 · 0 0

5x+10-6x+3=2x-2.

Group x's together, and group whole numbers together:

(5x-6x) + (10+3) = 2x-2

-x+13 = 2x-2

Add x to both sides:

13=3x-2

Add 2 to both sides:

15=3x

Divide by 3: 5=x

Check problem (plug in 5 where the problem said x and see whether the equation checks out):

5(5) + 10 - 6(5) +3 =?= 2(5) - 2

25 + 10 - 30 + 3 =?= 10 - 2

8 = 8.

2006-11-04 11:13:33 · answer #5 · answered by amy02 5 · 0 1

5x+10-6x+3=6-2x-2

1) make the equation to this 5x-6x+10+3= -2x+6-2
2) then do the math -x+13= -2x+4
3) subtract 13 from both side -x= -2x-9
4) add 2x on both side x= -9

2006-11-04 11:09:30 · answer #6 · answered by Zack C 3 · 0 2

5x+10-6x +3=6-2x-2.
First simplify the equation.
-1x+13=4-2x
Get like terms on the same side of the equation by doing the opposite function. If the number is positve then subtract.
-1x+13=4-2x
+1x +1x
13=4-1x
-4 -4
6=-1x
divide by -1
x=9

2006-11-04 11:07:08 · answer #7 · answered by Anonymous · 0 1

5x+10-6x+3=6-2x-2


-1x + 13 = 4 - 2x

Add +2x -13 to both sides to get x's on left and numbers on right:

+1x = - 9

x = -9

2006-11-04 11:05:10 · answer #8 · answered by fcas80 7 · 0 1

5x+10-6x+3=6-2x-2
0r, 5x-6x+2x=6-2-10-3
or, x=-9

simple

2006-11-04 11:04:43 · answer #9 · answered by Cool Guy 2 · 0 1

Whoring is faulty, and you will make some human beings experience like crap. To make your self quit doing it, think of of ways human beings might think of of you in the event that they discovered you probably did it. you will possibly finally end up getting the nickname "whore" or you need to be strolling around and you hear somebody say "ew examine out that whore'. I advise if it have been me being called a whore, i might experience particularly depressed and picture of why i replaced into stupid and did that.

2016-10-15 09:28:51 · answer #10 · answered by grabe 4 · 0 0

fedest.com, questions and answers